Pengaruh Akuntabilitas, Transparansi, Dan Sistem Pengendalian Internal Pemerintah Terhadap Kualitas Laporan Keuangan (Studi Kasus Pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Kabupaten Malaka Tahun 2021-2023) - Filibertha Yohana Iku They; Dwi Anggarani; Khojanah Hasan (CV. ITTC INDONESIA, 2025)
This study aims to examine the influence of accountability, transparency, and the government's internal control system on the quality of financial reports at the Malaka Regency Regional Financial and Revenue Management Agency (BPKPD) during 2021-2023. The method used was a quantitative survey approach, where data were obtained through questionnaires distributed to 37 respondents, consisting of officials and employees directly involved in regional financial management. Data analysis was conducted using classical assumption tests and multiple linear regression using SPSS version 25. The results indicate that partially, accountability has a positive and significant effect on the quality of financial reports. Transparency, although having a negative effect, did not show a significant effect. Meanwhile, the government's internal control system has a positive and significant effect on the quality of financial reports. Simultaneously, these three variables significantly influence the quality of financial reports. This finding underscores the importance of implementing sound accountability, optimizing transparency, and strengthening internal control systems in improving the quality of financial reports.